Bioluminescent and fluorescent reporter-expressing recombinant Akabane virus (AKAV): an excellent tool to dissect viral replication - Liu, Jingjing; Wang, Fang; Zhao, Jiangang; Qi, Yinglin; Chang, Jitao; Sun, Chao; Jiang, Zhigang; Ge, Junwei; Yin, Xin (Frontiers in Microbiology, 2024)
IntroductionAkabane virus (AKAV) is a worldwide epidemic arbovirus belonging to the Bunyavirales order that predominantly infects livestock and causes severe congenital malformations. Reporter-expressing recombinant virus represents a powerful tool to characterize the viral biology in vitro and in vivo.MethodsIn this study, we have successfully established a reverse genetics system for AKAV. The recued virus possessed similar growth characteristics to the parental virus in vitro. Moreover, the recombinant AKAV reporter viruses expressing nanoluciferase (Nluc) or mWasabi were constructed by inserting into S segment, named rAKAV-Nluc and rAKAV-mWasabi, respectively.ResultsWe investigated the virological characteristics of rAKAV-Nluc and rAKAV-mWasabi and found that rAKAV-Nluc displayed similar growth kinetics as the parental virus and could stably produce the nano-luciferase even after 10 rounds of serial passages. rAKAV-mWasabi also exhibited comparable growth kinetics and genetic stability as the parental virus. We further used the two reporter viruses to test the susceptibility of different cell lines to AKAV and found that cell lines derived from various host species, including human, swine, cattle, and monkey enables AKAV replication efficiently, accelerating our understanding of the AKAV cell tropism range.DiscussionTaken together, our established reverse genetics system for AKAV provides more convenient screening tools and can be used to study AKAV virulence and tropism, and to elucidate the molecular biology of AKAV.